Characterization of SARS-CoV-2 different variants and related morbidity and mortality: a systematic review. - SeyedAlinaghi, SeyedAhmad.; Mirzapour, Pegah.; Dadras, Omid.; Pashaei, Zahra.; Karimi, Amirali.; MohsseniPour, Mehrzad.; Soleymanzadeh, Mahdi.; Barzegary, Alireza.; Afsahi, Amir Masoud.; Vahedi, Farzin.; Shamsabadi, Ahmadreza.; Behnezhad, Farzane.; Saeidi, Solmaz.; Mehraeen, Esmaeil.; Shayesteh Jahanfar, . (Tufts University. Tisch Library., 2021)
Keywords: Variants, Strains, Genomic diversity, Characterizations, SARS-CoV-2, COVID-19.; Springer Open.